Pendidik Karakter yang Memotivasi dan Menginspirasi - Tampubolon, Simon Mangatur (Bina Nusantara University, 2014)
Article discusses how character educators in universities meet the challenges of character education in college. This article describes how the character educators in college should be educators who motivate and inspire. It is as a response to the challenges that the characters have already been formed in the students themselves. Article describes contemplation, principles, and patterns to be the educators of character who motivate and inspire character.